2020
DOI: 10.1111/cei.13496
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-based graft-versus-host disease prophylaxis increases the immunosuppressivity of myeloid-derived suppressor cells without affecting T cells and anti-tumor cytotoxicity

Abstract: The immunosuppressant rapamycin (RAPA) inhibits mammalian target of rapamycin (mTOR) functions and is applied after allogeneic bone marrow transplantation (BMT) to attenuate the development of graft-versus-host disease (GVHD), although the cellular targets of RAPA treatment are not well defined. Allogeneic T cells are the main drivers of GVHD, while immunoregulatory myeloid-derived suppressor cells (MDSCs) were recently identified as potent disease inhibitors. In this study, we analyzed whether RAPA prevents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…One day before BMT, B6.bm1 recipient mice received total body irradiation with 12 Gy split in two doses 3 h apart from a 137 Cs source. BM cells were depleted from T cells as described previously ( 18 , 19 ). Mice were intravenously reconstituted with 5 × 10 6 T-cell-depleted BM (TCD-BM) in the presence or absence of 2 × 10 7. spleen cells (SC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One day before BMT, B6.bm1 recipient mice received total body irradiation with 12 Gy split in two doses 3 h apart from a 137 Cs source. BM cells were depleted from T cells as described previously ( 18 , 19 ). Mice were intravenously reconstituted with 5 × 10 6 T-cell-depleted BM (TCD-BM) in the presence or absence of 2 × 10 7. spleen cells (SC).…”
Section: Methodsmentioning
confidence: 99%
“…The original contributions presented in the study are publicly available and are based on JS's dissertation: ( 60 ). mRNA Seq data can be found here: .…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies showed that rapamycin was able to induce G-MDSCs accumulation with an enhanced immunosuppressive role in the presence of aGVHD, via upregulation of ARG1 and iNOS and induction of regulatory T cells. Graft-versus-tumor effect was maintained [ 57 , 58 ].…”
Section: Gvhd Pathophysiology and Implications For Mdscsmentioning
confidence: 99%
“…In addition, under inflammatory conditions, T Regs may promote immunosuppression by the differentiation of MDSC toward M-MDSCs ( p < 0.01, ANOVA and Tukey post-test) [ 101 ]. The use of rapamycin is shown to be feasible in aGVHD management when the immunosuppressive capacity of MDSCs needs to be strengthened without impairing T cell-mediated fitness [ 57 , 58 ]. Supported by these data, it is logical for someone to consider that the adoptive transfer of a product containing both mobilized MDSCs and T Regs may provide greater benefit for achieving immune tolerance than either alone.…”
Section: Mdscs As Diagnostic or Therapeutic Targets In Gvhdmentioning
confidence: 99%